La falta de estimulación temprana y su incidencia en el desarrollo de la motricidad gruesa de los niños de 3 y 4 años que asisten al centro de desarrollo infantil “las abejitas” de la ciudad de quito. Período 2015. Lineamientos propositivos. Terapia psicomotriz - Tapia Capa, Jenny Marlene (2015)
This thesis entitled: "THE LACK OF EARLY STIMULATION AND ITS IMPACT ON THE DEVELOPMENT OF GROSS MOTOR SKILLS OF CHILDREN 3 AND 4 YEARS ATTENDING THE CENTER OF DEVELOPENMENT INFANTILE “LAS ABEJITAS” CITY OF QUITO. PERIOD 2015 GUIDELINES PROACTIVE. PSYCHOMOTOR THERAPY" is structured and developed according to regulations graduation National University of Loja. In Ecuador, 6 of every hundred children have gross motor delays in Quito percentages fluctuate in similar terms. A place where you can clearly demonstrate this type of problem is the Child Development Center "The Beehive" of Quito, the same that is located in the Santa Anita 2 Oe5p Citadel and El Canelo, which acts as childcare and home to children 2-5 years of age, who are mostly middle social status, this organization was created in January 2000, which has been operating at the time 15 years. The general objective that guided the research was: To determine the influence of the lack of early stimulation in the development of gross motor skills of children 3 and 4 years old who attend the Center of development “Las Abejitas”. The methods used for the preparation of this research work were: Scientist, Inductive, Deductive, Descriptive and Statistical Model; techniques used were: A Survey aimed at teachers and parents of children 3-4 years attending the Child Center of development “las Abejitas” city of Quito, in addition to managing an observation guide to establish implementation of early learning activities, to assess the gross Motor. 29.4% of teachers engaged in moving for children / as, 23.5% do balance exercises, jumping 17.6% children, 17% down stairs and finally up 11.8% stairs. Valued Development Gross Motor of children from 3-4 years of age attending Center development “Las Abejitas”, the following results were obtained: as many aspects are on the scale of good, a smaller percentage with difficulty, and a small percentage fine, the scale is not minimized. It follows that the major problems lie in aspects of scale, "only with difficulty", therefore will face therapy helps these 5 aspects, they are: Walking, balance, rhythm, jump, climb, climb, movement coordination, body awareness.